THE ABILITY OF LANGUAGE SKILLS OF AN AUTISTIC STUDENT: A Case Study by 7 Year Autistic Student - Romaida Lubis; Rahmad Husein; Sumarsih Sumarsih (Universitas Negeri Medan, 2019)
This research aims to describe the ability of active/expresive language and passive/ reseptive language of an autistic student and the effort to improve the language itself helped by the teacher and the shadow teacher in a non-govermental school in Medan. This research uses qualitative descriptive with study case of an autistic student in primary second grader , his initial is FR. Technique of data collection are observation, interview, and documentation. Technique of data analysis are data condensation, data display and verification and conclusion. The result of research showed that the ability of active/expressive language of FR still had difficulties in pronouncing, unclear articulation for certain letter such as r, n, ny, l, talk simple, unable to have interaction and communication properly, unable to convey the information, requesting what he needed use incomplete sentence when he got depresion, he needed help in writing. And the ability of passive/ receptive FR still have difficulties to comprehend the sentence he heard, able to understand simple sentence only based on his daily experience, able to answer simple sentence when the question asked is same with the statement, respond the long questions by replying the last sentence only, unable to comprehend the reading. Keyword: Active/expressive, passive/receptive, autistic